2008
DOI: 10.1080/14616690701744364
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Perspective on Intergenerational Support

Abstract: It has often been argued that Southern European countries are more familialistic in their culture than Western and Northern European countries. In this paper, we examine this notion by testing the hypothesis that adult children are more responsive to the needs of their elderly parents in countries with more familialistic attitudes. To test this hypothesis, we analyse the Survey of Health, Ageing and Retirement in Europe (SHARE). We focus on three indicators of need: (a) the partner status of the parent, (b) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(125 citation statements)
references
References 39 publications
5
106
0
14
Order By: Relevance
“…People in need of assistance will be given support and are not expected to do anything in return (Krebs, 1970). In line with this perspective, research has shown that children respond to their parents' need for support, where factors like partnership status, health, educational level and financial position are frequently used as indicators of need for support (Eggebeen & Davey, 1998;Grundy, 2005;Kalmijn & Saraceno, 2008). When applying this principle to the retirement transition, it can be expected that the more support parents need upon retirement, the more support they will receive from their children (Hypothesis 1: the need hypothesis).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…People in need of assistance will be given support and are not expected to do anything in return (Krebs, 1970). In line with this perspective, research has shown that children respond to their parents' need for support, where factors like partnership status, health, educational level and financial position are frequently used as indicators of need for support (Eggebeen & Davey, 1998;Grundy, 2005;Kalmijn & Saraceno, 2008). When applying this principle to the retirement transition, it can be expected that the more support parents need upon retirement, the more support they will receive from their children (Hypothesis 1: the need hypothesis).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It has been typical to describe patterns of exchange in European families in terms of a North-South gradient (Albertini, Kohli and Vogel 2007;Hank 2007;Kalmijn and Saraceno 2008;Ogg and Renaut 2006). Intergenerational transfers of time and money among family members tend to be less frequent in the Nordic than in the Southern European countries, with the Continental European countries being somewhere in the middle.…”
Section: East-west Differences In Intergenerational Family Patterns Amentioning
confidence: 99%
“…They not only reflect the cultural climate in which people live (Daatland and Herlofson 2003;Kalmijn and Saraceno 2008), but also the individual circumstances in which they find themselves (Gans and Silverstein 2006). Family norms are of interest because they are predictive of intergenerational support behaviour: they predispose people to behave in a certain way towards their family members.…”
Section: Preferences Predicting Behaviour In Familiesmentioning
confidence: 99%
“…Cette question revêt pourtant une pertinence grandissante dans les pays à tradition libérale anglosaxonne, comme le Canada, où le sentiment d'obligation filiale apparaît être affaire de négociation plutôt que de devoir entre parents âgés et enfants devenus adultes, et ce, alors que l'État cherche à renvoyer à la famille les responsabilités d'aide à ses membres âgés (Daatland et Herlofson, 2003 ;Kalmijn et Saraceno, 2008). Jusqu'à tout récemment, il n'y avait peut-être pas lieu de s'inquiéter des répercussions de la baisse de la fécondité et de la montée de l'instabilité conjugale sur la prise en charge des aînés, les personnes âgées d'aujourd'hui étant relativement nombreuses à n'avoir connu qu'une seule union, un mariage ayant de plus donné lieu à une descendance passablement nombreuse.…”
Section: Changements Démographiques Et Trajectoires Fami-lialesunclassified